2022
DOI: 10.1109/access.2022.3147447
|View full text |Cite
|
Sign up to set email alerts
|

Discover Customers’ Gender From Online Shopping Behavior

Abstract: Gender information is very important for the recommendation system in the online shopping website. However, gender data often face label missing and incorrect labelling problems caused by consumers' unwillingness to actively disclose personal information, which leads to gender estimation results that cannot meet the needs of the product recommendation system. To discover the customers' gender information, we explore the customers' online shopping behavior, especially the items viewed in the shopping session, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
0
0
Order By: Relevance
“…Wang and Zhang used the fully modified ordinary least squares method to find that the increase in R&D investment contributes to the decoupling of environmental pressure and economic growth [61]. Li and Li conclude that energyrelated investments increase CO 2 emissions over all of China by constructing a spatial econometric model [62]. Andreoni and Galmarini used exponential decomposition to analyze the driving factors of CO 2 produced by energy in 33 countries, and found that economic growth is the main driving factor [63].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wang and Zhang used the fully modified ordinary least squares method to find that the increase in R&D investment contributes to the decoupling of environmental pressure and economic growth [61]. Li and Li conclude that energyrelated investments increase CO 2 emissions over all of China by constructing a spatial econometric model [62]. Andreoni and Galmarini used exponential decomposition to analyze the driving factors of CO 2 produced by energy in 33 countries, and found that economic growth is the main driving factor [63].…”
Section: Literature Reviewmentioning
confidence: 99%